2001
DOI: 10.1002/eat.1084
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to treatment for eating disorders among ethnically diverse women

Abstract: Abstract:Objective: This study examined barriers to treatment in an ethnically diverse community sample of women with eating disorders. Method: Participants were 61 women (22 Hispanics, 8 Asians, 12 Blacks, 19 Whites) with eating disorders. Diagnosis was determined using the Eating Disorder Examination. Treatment-seeking history, barriers to treatment seeking, ethnic identity, and acculturation were assessed. Results: Although 85% of the sample reported wanting help for an eating problem, only 57% had ever sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
174
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 39 publications
13
174
0
3
Order By: Relevance
“…However, our data also indicate that currently few Latinos with eating disorder symptoms have ever received any treatment and only a fraction got any healthcare in the past year. This is consistent with previous research indicating that Latinos underutilize mental health services, 31 particularly those who have resided in the US for a short period of time. 31,32 Several limitations are evident, including the unstable prevalence estimates and the small sample sizes, which raise concern about adequate power to detect meaningful differences in this sample.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, our data also indicate that currently few Latinos with eating disorder symptoms have ever received any treatment and only a fraction got any healthcare in the past year. This is consistent with previous research indicating that Latinos underutilize mental health services, 31 particularly those who have resided in the US for a short period of time. 31,32 Several limitations are evident, including the unstable prevalence estimates and the small sample sizes, which raise concern about adequate power to detect meaningful differences in this sample.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with previous research indicating that Latinos underutilize mental health services, 31 particularly those who have resided in the US for a short period of time. 31,32 Several limitations are evident, including the unstable prevalence estimates and the small sample sizes, which raise concern about adequate power to detect meaningful differences in this sample. Diagnoses were also based on unvalidated, fully structured lay interviews where lifetime prevalence was assessed retrospectively.…”
Section: Resultssupporting
confidence: 92%
“…In line with the research demonstrating the influence of ethnicity on help-seeking characteristics, two recent studies showed low rates of treatment seeking in an ethnically diverse sample of individuals with eating disorders. 42,43 Another study found that black women were significantly less likely than white women to have received treatment for binge eating disorders. 44 Moreover, a recent study indicated that physicians were significantly less likely to inquire about eating disorder symptoms among ethnic minorities than among nonminority patients.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Prevalence estimates of eating disorders among ethnic minorities are inconsistent. Some studies show lower levels of eating disorders for Asian Americans compared to Whites, whereas other studies show higher levels of eating disorders among Asian American women.…”
Section: Introductionmentioning
confidence: 99%